D-107 Vaccination establishes CXCR5+PD1+CD4+ peripheral blood germinal center T follicular helper cell relatives in humans. (January 2016) - Schmitz, Frank; Gerdts, Sarah; Flach, Britta; Moore, Miranda; Perkins, Jonathan; Robins, Harlan; Aderem, Alan; Spearman, Paul; Tomaras, Georgia; De Rosa, Stephen; McElrath, M. Juliana; Heit, Antje
Abstract : Protective vaccines against microbial pathogens are designed to elicit long-lasting antigen-specific T- and B-cell responses. CD4+ T follicular helper cells (Tfh) are specialized in supporting and selecting higher affinity B cells during the germinal center (GC) reaction in lymph nodes. Thus, the identification of a circulating Tfh relative with a potential role in this process is an area of intense interest, particularly if their properties provide insight into how the antibody response is shaped. Recently, functional counterparts of GCTfh cells were identified within the pool of circulating CXCR5+ CD4 memory T cells. To understand whether such cells are induced following vaccination we used additional markers for GCTfh, PD1 and ICOS, to stratify circulating CXCR5+ Tfh subsets into three distinct subsets and followed them longitudinally upon vaccination to investigate their diversity, kinetics, and ontogeny. Analysis of the T-cell receptor clonal repertoire revealed a clonal relationship between circulating, PD1-expressing subsets and tonsillar GCTfh cells. Furthermore, a vaccine-specific PD1+ICOS+ subset clonally expanded one week after vaccine boost, correlated with vaccine-specific IgG serum antibodies, phenotypically resembled GCTfh cells and showed a clonal relationship to persistent PD1+ICOS- memory cells. Thus, vaccination establishes Tfh relatives in circulation that expand upon antigen reencounter with the potential to serve as early, cellular marker for GC activity upon vaccination.